Glasoslovje, besedoslovje in besedotvorje v delih Jakoba Riglerja - Marina Bajić; Zorko, Zinka; Koletnik, Mihaela (2003)
Phonology, Vocabulary and Verbal Formation in the Works of Jacob Rigler. No abstract.